On Finding Language for What It Means to Be Alive Today: Notes on A Living Poem at MoMA. - Stiles, Sasha (World Literature Today)
The article reviews the multimedia exhibition "A Living Poem", showcased at the Museum of Modern Art in New York and in Seoul, which blends human creativity with artificial intelligence to create continuously evolving poetic performances.